What It Really Means to Be Accomplishment Based. Issue 4 (April 2017) - Binder, Carl
Abstract : Human performance technology (HPT) evolved with the shift from a focus on behavior to accomplishments, the valuable products of behavior. The term accomplishment has not always been used consistently over the years, to the detriment of the field. This article summarizes benefits of accomplishment‐based performance improvement, reviews Joe Harless's recently republished book, The Eden Conspiracy, about accomplishment‐based educational reform, and summarizes successful educational reforms that have emerged from Eden in nearly 20 years since its original publication.